Sykloksidiimillä hyvä torjuntateho metsänlauhaa vastaan - Kiljunen, Nuutti (Metsäntutkimuslaitos, 2006)
Selostus artikkeleista: Dixon, F.L., Clay, D.V. & Willoughby, I. 2005. The relative efficacy of herbicides for control of Deschampsia flexuosa (L.) in woodland establishment in the UK. Forestry 78(3): 229-238. Dixon, F.L., Clay, D.V. & Willoughby, I. 2005. The tolerance of young trees to applications of clopyralid alone and in mixture with foliar-acting herbicides Forestry, 78(4): 353- 364.
Keywords: metsälauha; sykloksidiimi; torjunta-aineet